Ginsenoside-Rb1 for Ischemic Stroke: A Systematic Review and Meta-analysis of Preclinical Evidence and Possible Mechanisms - Shi, Yi-Hua; Li, Yan; Wang, Yong; Xu, Zhen; Fu, Huan; Zheng, Guo-Qing (Frontiers in Pharmacology, 2020)
Abstract Background: Ischemic stroke is the most common type of stroke while pharmacological therapy is limited. Ginsenosides are the major bioactive compounds in Ginseng and have been found to have various pharmacological effects in the nervous system. In the present study, we sought to evaluate the effects of Ginsenoside-Rb1 (G-Rb1), an important ingredient of ginsenosides, and the probable neuroprotective mechanisms in experimental ischemic strokes. Methods: Studies of G-Rb1 on ischemic stroke animal models were identified from 7 databases. No clinical trials should be included in the analysis. The primary outcome measures were neurological function score, infarct volume, evans blue content and/or brain water content (BWC). The second outcome measures were the possible neuroprotective mechanisms. All the data were analyzed by Rev Man 5.3. Result: Pooled preclinical data showed that compared with the controls, G-Rb1 could improve neurological function (Zea Longa (n = 367, P < 0.01); mNSS (n = 70, P < 0.01); Water maze test (n = 48, P < 0.01); Bederson (n = 16, P < 0.01)), infarct area (TTC (n = 211, P < 0.01); HE (n = 26, P < 0.01)), as well as blood-brain barrier function (BWC (n = 64, P < 0.01); Evans blue content (n=26, P<0.05)). It also can increase BDNF (n = 26, P < 0.01), Gap-43 (n = 16, P < 0.01), SOD (n = 30, P < 0.01), GSH (n = 16, P < 0.01), Nissl-positive cells (n = 12, P < 0.01), Nestin-positive cells (n = 10, P < 0.05), and reduce Caspase-3 (n = 36, P < 0.01), IL-1 (n = 32, P < 0.01), TNF-α (n = 72, P < 0.01), MDA (n = 18, P < 0.01), NO (n = 44, P < 0.01), NOX (n = 32, P < 0.05), ROS (n = 6, P < 0.05), NF-κB (P < 0.05) and TUNEL-positive cells (n = 52, P < 0.01). Conclusion: Available findings demonstrated the preclinical evidence of G-Rb1 that has a potential neuroprotective effect, largely through attenuating brain water content, promoting the bioactivities of neurogenesis, anti-apoptosis, anti-oxidative, anti-inflammatory, energy supplement and cerebral circulation.